Peran Orang Tua dalam Meningkatkan Kemandirian Anak Pada Kegiatan Belajar di Rumah di TK X - Ade Iis Kurniawati (Jurnal Riset Pendidikan Guru Paud, 2021)
Abstract. This study was conducted with the aim of describing how the role of parents in increasing children's independence in learning activities at home is carried out through daily worship activities, learning activities, self help activities and parental barriers in instilling independence in children at home. The research method used is descriptive qualitative method to describe the role of parents in increasing children's independence in learning activities at home according to the condition of the child at home which is currently experiencing a pandemic. Data collection techniques in this study include interviews, observation and documentation. The results in the research that have been obtained are in the form of an overview of the way the role of parents in instilling children's independence which consists of how parents instill children's independence in daily worship activities while at home such as (prayer, recite the Koran, behave well and others), the way people parents instill children's independence in online learning activities such as (reading, writing, counting, singing and others), the way parents instill children's independence in self-help activities such as (learning to write alone, eating and drinking alone, learning to recite alone, wearing own clothes). and others) as well as obstacles for parents in instilling children's independence during learning at home such as (busy working as a housewife, busy working there is a duty as a teacher, environmental conditions and so on). Abstrak. Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan tentang cara peran orang tua dalam meningkatkan kemandirian anak pada kegiatan belajar di rumah yang dilakukan melalui kegiatan ibadah harian, kegiatan belajar, kegiatan self help serta hambatan orang tua dalam menanamkan kemandirian pada anak di rumah. Metode penelitian yang digunakan adalah metode kulitatif deskriptif untuk menggambarkan peran orang tua dalam meningkatkan kemandirian anak pada kegiatan belajar di rumah sesuai dengan kondisi anak di rumah yang pada saat ini sedang pandemin. Teknik pengumpulan data dalam penelitian ini meliputi wawancara, observasi dan dokumentasi. Hasil dalam penelitian yang telah di dapat berupa gambaran mengenai cara peran orang tua dalam menanamkan kemandirian anak yang terdiri dari cara orang tua menanamkan kemandirian anak dalam kegiatan ibadah harian selama di rumah seperti (shalat, mengaji, berperilaku baik dan lain-lain), cara orang tua menanamkan kemandirian anak dalam kegiatan belajar onlinen seperti (membaca, menulis, berhitung, bernyanyi dan lain-lain), cara orang tua menanamkan kemandirian anak dalam kegiatan self help seperti (belajar menulis sendiri, makan minum sendiri, belajar mengaji sendiri, memakai baju sendiri dan lain-lain) serta habatan bagi orang tua dalam menanamkan kemandirian anak pada masa belajar di rumah seperti (sibuk bekerja menjadi ibu rumah tangga, sibuk bekerja ada yang bertugas menjadi guru, kondisi lingkungan dan sebagainya).